NU CORPORATE WEB PORTAL - Rakhay, Nurali; Mukayev, Olzhas; Fazyl, Yelaman; Kanatuly, Daulet; Bagdat, Dinmukhammed (Nazarbayev University School of Engineering and Digital Sciences, 2025)
This is a project for the Nazarbayev University Community, including students, professors, administration and other staff, named NU Corporate Web Portal. Aim of the project is to streamline the administrative tasks of the university and needs of students by automating the management of events, clubs, user profiles and providing communication channels. The team ensured that the portal is friendly for end users and provided data in multiple languages including Kazakh, Russian and English to make the platform accessible. The authentication is provided by MS Azure SSO that enables secure access to the platform features. Those features are: centralized events calendar, news page for users to write articles, and a phonebook with different filters. The tech stack used to build the platform is React.js, Spring Boot and PostgreSQL.
Keywords: type of access: open access